2023
DOI: 10.3389/fbioe.2023.1301430
|View full text |Cite
|
Sign up to set email alerts
|

Liquid platelet-rich fibrin produced via horizontal centrifugation decreases the inflammatory response and promotes chondrocyte regeneration in vitro

Huimin Li,
Ting Xia,
Hao Zeng
et al.

Abstract: Objective: Recently, liquid platelet-rich fibrin (PRF), a rich source of concentrated platelets and growth factors, has emerged as a promising agent for stimulating tissue regeneration. However, its specific efficacy in chondrocyte proliferation and cartilage regeneration remains underexplored. To address this question, we investigated liquid PRF obtained through horizontal centrifugation and compared its effects with hyaluronic acid (HA), a high molecular weight glucosamine supplement widely used in clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, in the present study, even with a high quantity of platelets, cell proliferation remained similar when using high-or low-RCF PRF. Moreover, various studies have demonstrated that the presence of leukocytes in PRF also contributes to its regenerative properties through the release of additional growth factors and the modulation of the inflammatory response [31][32][33][34]. Future studies should explore the use of different protocols for specific clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, even with a high quantity of platelets, cell proliferation remained similar when using high-or low-RCF PRF. Moreover, various studies have demonstrated that the presence of leukocytes in PRF also contributes to its regenerative properties through the release of additional growth factors and the modulation of the inflammatory response [31][32][33][34]. Future studies should explore the use of different protocols for specific clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Sections of 3–4 µm were then created using a rotary microtome (Leica RM2255; Wetzlar, Germany) and stained using hematoxylin and eosin staining (H&E) for a general evaluation of the cell distribution. Additional sections were stained using specific immunohistochemical antibodies to identify platelets (CD 61) and leukocytes (CD45) using an Autostainer (Lab Vision™ Autostainer 360, Thermo Scientific, Waltham, MA, USA) following previously published methods [ 4 , 18 ]. The CD-61 antibody (1:100 [ab225742]) and CD-45 antibody (1:100 [ab10558]) were used as primary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…PRF is already being applied in various fields of regenerative medicine, showing considerable clinical success [ 13 , 14 ]. Additionally, different preclinical studies have been conducted to understand the regenerative properties of PRF and reported a positive influence on cell viability, proliferation, and differentiation in vitro [ 15 , 16 , 17 , 18 ]. Furthermore, several studies of our group have addressed the influence of the applied relative centrifugal force (RCF) during the centrifugation of PRF matrices on PRF components and bioactivity.…”
Section: Introductionmentioning
confidence: 99%